(untitled) (Bulletin of the International Association for Paleodontology, 2024)
Existing bioarchaeological studies have not deeply explored the analytical characterization of the chemical structure of dentine. Accordingly, this study used ATR-FTIR to analyze the dentine of 30 human teeth from six archaeological sites in Jordan dated from the Early Roman to the Early Byzantine periods. Besides collagen cross-linking, the factors (ratios) that may influence the strength of dentine were also analyzed and include the ratios of phsphate/amide I, crbonate/phosphate, and A-type cabonate/B-type carbonate. The results of the study point to statistically insignificant diffrences in the factors affectng tensile strength of dentine and thus teeth loading on the site level, while a statistically significan one is found among sites. The differences in these ratios is found to be attributed tooth loading and age at death.